2019
DOI: 10.1158/0008-5472.can-19-0585
|View full text |Cite
|
Sign up to set email alerts
|

Banding Together: A Systematic Comparison of The Cancer Genome Atlas and the Mitelman Databases

Abstract: Cytogenetic aberrations at the single-cell level represent an important characteristic of cancer cells relevant to tumor evolution and prognosis. However, with the advent of The Cancer Genome Atlas (TCGA), there has been a major shift in cancer research to the use of data from aggregate cell populations. Given that tumor cells harbor hundreds to thousands of biologically relevant genetic alterations that manifest as intratumor heterogeneity, these aggregate analyses may miss alterations readily observable at s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 23 publications
2
8
0
Order By: Relevance
“…The notebooks compare the frequencies of copy number changes in the Mitelman DB with those calculated from TCGA data for three well‐known deletions: breast cancer (Chromosome 1), kidney adenocarcinoma (Chromosome 3), and acute myeloid leukemia (Chromosome 5). In agreement with Denomy et al 14 we found similar patterns of gains and losses in the two data sets (Figure 5). Moreover, Table S1 (Supplementary material) shows the Pearson correlation of frequencies computed from Mitelman DB and TCGA‐BRCA for each chromosome.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The notebooks compare the frequencies of copy number changes in the Mitelman DB with those calculated from TCGA data for three well‐known deletions: breast cancer (Chromosome 1), kidney adenocarcinoma (Chromosome 3), and acute myeloid leukemia (Chromosome 5). In agreement with Denomy et al 14 we found similar patterns of gains and losses in the two data sets (Figure 5). Moreover, Table S1 (Supplementary material) shows the Pearson correlation of frequencies computed from Mitelman DB and TCGA‐BRCA for each chromosome.…”
Section: Resultssupporting
confidence: 93%
“…Moreover, Table S1 (Supplementary material) shows the Pearson correlation of frequencies computed from Mitelman DB and TCGA‐BRCA for each chromosome. According to the analysis, most of the significant correlations of Table S1 are also significant in the results of Denomy et al 14 with few exceptions, likely due to different resolution levels.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…The rearrangement produces a fused tyrosine kinase signaling protein that directly affects the cell cycle, frequently causing chronic myelocytic leukemia and, less frequently, acute lymphoblastic leukemia. Chromosome rearrangements and genome instability are now considered as hallmarks of cell transformation, with hundreds of signature rearrangements identified in human cancers (49). Recently, genomic techniques have been used to study cancer genomes on a large scale (50), confirming and dramatically extending earlier findings.…”
Section: Chromosomal Rearrangements That Affect Phenotypementioning
confidence: 59%
“…The database is searchable by a wide variety of fields, such as patient age, publication authors, gene, tumor histology, tissue type, mutation recurrence, associated clinical features, and cancer types. 255 …”
Section: Fusion Oncogene Databasesmentioning
confidence: 99%